Methodological and Ontological Principles of Observation and Analysis
1 online resource
Keywords: In our daily experiences, we feel, perceive, designate, invoke or comment on a plurality of beings: people, artifacts, technologies, institutions, projects, animals, divinities, emotions, cultures, ideologies or opinions that are part of our world. While these beings are all part of our world, they present various forms of existence. Echoing recent developments in existential anthropology, Communication as Constitutive of Organization (CCO) research, and Actor Network Theory, here scholars from a variety of disciplines discuss how they study the types of beings that have been at the core of their respective research. Reflecting on the specific mode of existence, presence and action of the being they follow, they reveal the methodological innovations they deploy in order to analyze excerpts of field notes, filmed interactions, conversations, pictures, newspapers, narratives, etc.